Assessing and Treating Anxiety Disorders in Young Children The Taming Sneaky Fears Program - Monga, Suneeta (Springer International Publishing, 2018)
This book examines assessment and treatment methods for anxiety disorders in four- to- seven-year-olds. It discusses risk and protective factors in the preschool years, comorbidities, and how conditions such as separation anxiety disorder, social anxiety disorder, and selective mutism present in this age group. The book examines limitations of current definitions, assessment methods, and interventions. Chapters offer a theoretical framework from which to understand how traditional cognitive-behavior therapy (CBT) strategies can be used effectively in this age group. It offers a detailed description of the Taming Sneaky Fears program, an innovative, evidence-based group CBT program for four- to seven-year-old anxious children and their parents. It provides step-by-step instructions on how to implement Taming Sneaky Fears. The book concludes by addressing common challenges, influences, and outcomes for four- to seven-year-old anxious children and their families and provides recommendations for reducing the barriers to healthy development. Topics featured in this book include: Screening and assessment tools for young anxious children. Innovative assessment approaches for young anxious children. The use of Bravery Ladders to teach young children to overcome their fears and anxieties. Specific adaptations of the Taming Sneaky Fears program for selective mutism and social anxiety disorder. The pivotal role of parents in the success of the Taming Sneaky Fears program. Assessing and Treating Anxiety Disorders in Young Children is a must-have resource for researchers, clinicians and related professionals, and graduate students in child and school psychology, pediatrics, social work, and psychiatry.